USERS ACCEPTANCE OF LOCATION-BASED MARKETING APPS IN TOURISM SECTOR: AN EXPLORATORY ANALYSIS - Pedro Palos-Sanchez; Jose Ramon Saura; Ana Reyes-Menendez; Ivonne Vásquez Esquivel (Journal of Spatial and Organizational Dynamics, 2018)
Mobile devices are the most used technology tools to access the Internet since they allow access from anywhere. This possibility has prompted companies to focus, to a greater extent, strategies based on geolocation marketing. Geolocation is a tool through which people or places can be located and have very diverse functionalities and applications. Location-Based Services (LBS) allow businesses to incorporate these types of tools into their digital marketing strategies. Social networks based on location services (LBSNS or Location-Based Social Network System) allow businesses to access information on the location of customers in real time. The present study provides more information on LBS and geolocation marketing, also known as geomarketing, analyzing the utility and benefits that this tool has to digital marketing and social networks and the importance of its technological adoption. To achieve this objective, a thorough review of technology adoption literature was carried out and a series of interviews were made with experts and professionals in its two aspects: digital marketing and information technologies. The results show the way in the tourism sector, these tools are managed, the means in which they are active, the LBS systems used, the utility and benefits they perceive from them, as well as the importance and efforts that they dedicate to them. This study reaches relevant conclusions for tourism professionals interested in incorporating LBS and geomarketing strategies into their businesses, as well as researchers interested in the behavior in Location-Based Services.